Cicero’s corpus and Petrarca’s ankle. The theory of imitatio and its practice - Marnoto, Rita (2020)
This article focuses on the centrality provided to auctores and texts as corpora, in the framework of Francesco Petrarca and the theory of imitation by the humanists. Initially, animal images from Petrarca and the humanists are analysed, as well as the paths of their diffusion. These were used to express the role of the model, the involvement of the writer, variatio, the election of stilus, and the questions sustained by the new routes of interaction with Cicero. Then, three main methodological ways to study the relationship between texts as corpora are presented: semiosphere, intertextuality, and reception theory. A critic point of view towards the static methodologies is here expressed. Conclusively, the dialogue between Petrarca and Cicero, as text and corpus, is recalled in order to incorporate the auctores contamination.